2021
DOI: 10.1029/2020jd033855
|View full text |Cite
|
Sign up to set email alerts
|

A Four‐Parameter Model for Estimating Diurnal Temperature Cycle From MODIS Land Surface Temperature Product

Abstract: Land surface temperature (LST) plays a critical role in the land-atmosphere interactions. It is a key parameter in estimation of soil moisture, evapotranspiration, and earth radiation budget from satellite observations, and soil thermal regimes. However, in some applications, its diurnal cycle (Land Surface Diurnal Temperature Cycle [LSDTC]) is more meaningful, such as estimation of surface energy and mass exchanges at the land-atmosphere interface (Nemani & Running, 1989), examining surface urban heat islands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Their RMSE results showed less than 1.06 • C. Sismanidis et al quantified the daily and annual dynamics of LST obtained from satellites and stated that the Earth's diurnal and annual cycles drive the changes of LST in space and time, but their combined effects are transferred differently from place to place as a function of weather, local weather conditions, and surface characteristics [50]. Lu and Zhou presented a 4-parameter model to estimate the LST diurnal cycle using MODIS LST [51]. They showed that their model can record the changes of LST during a day very well.…”
Section: Introductionmentioning
confidence: 99%
“…Their RMSE results showed less than 1.06 • C. Sismanidis et al quantified the daily and annual dynamics of LST obtained from satellites and stated that the Earth's diurnal and annual cycles drive the changes of LST in space and time, but their combined effects are transferred differently from place to place as a function of weather, local weather conditions, and surface characteristics [50]. Lu and Zhou presented a 4-parameter model to estimate the LST diurnal cycle using MODIS LST [51]. They showed that their model can record the changes of LST during a day very well.…”
Section: Introductionmentioning
confidence: 99%